Effects of vacancies on the electronic structures and photocatalytic properties of g-C3N4. (December 2022) - Sun, S.P.; Wang, Y.R.; Gu, S.; Wang, B.; Sun, J.H.; Jiang, Y.
Abstract: The geometric structures, electronic structures and photocatalytic properties of g-C3 N4 with different vacancies are studied by the first-principles calculations. These calculations suggest that introducing different vacancies can cause the relaxation of these adjacent atoms, the formation of dangling bonds, and the deformation of these building blocks. And these band gaps of the heptazine-based graphitic C3 N4 sheets are narrowed by different vacancies. The energetic preferability of the heptazine-based g-C3 N4 sheets with different vacancies is assessed as functions of the environmental factors, including nitrogen partial pressure and temperature. It is indicated that VC2 and VN2 are the respectively stable vacancies over the investigated nitrogen partial pressure. A transition from VN2 to VC2 should occur at ultrahigh vacuum p N 2 ≥ ∼ 10 − 23 a t m at 1000 K, and move to higher nitrogen partial pressure with the increasing temperature. According to the calculated absorption coefficient, these g-C3 N4 sheets with VC2 and VN2 vacancies have larger absorption than the perfect structure over the visible wavelength range, suggesting that vacancies can increase the catalytic efficiency of graphitic C3 N4 . These results show that introducing defects, especially vacancies, is an effective approach to enhance the sunlight absorption efficiency of graphitic carbon nitride. Highlights: The dependence of vacancy type on the environmental factors is revealed. The graphitic CN sheets with VC2 and VN2 are respectively stable. The band gaps of graphitic CN sheets can be narrowed by different vacancies. The graphitic CN sheets with VC2 and VN2 have improved light absorption properties.